Second-line therapy of advanced ovarian cancer with GnRH analogs. Issue 5 (1st August 2004) - Balbi, G.; Piano, L. D.; Cardone, A.; Cirelli, G.
Abstract : Ovarian cancer is still the first cause of death among female malignancies. The standard treatment adopted in ovarian cancer is a radical surgical treatment or cytoreduction, followed by six courses of platinum-based chemotherapy; second-line regimens are associated with severe side effects. GnRH analogs could represent an alternative therapeutical approach. The aim of our study was to evaluate the role of GnRH analogs in the management of platinum-resistant ovarian cancers. We enrolled 12 patients affected by advanced ovarian cancer, previously treated with six courses of platinum–paclitaxel. In second-line therapy, we used leuprolide on 1, 8, and 28 days of treatment. CA 125 levels were recorded for each patient. One case of clinical partial response was obtained (8.3%). Stable disease was diagnosed in three patients (25%). Progression was recorded in eight cases (66.7%). Progression-free survival was 6 months. The treatment was well tolerated by patients. The high tolerability and the results obtained with leuprolide versus platinum in second-line therapy might permit a better use of the analogs for advanced ovarian cancer.